Response to heat stress and glutenins allelic variation effects on quality traits in durum wheat - Tabbita, Facundo; Ammar, Karim; Ibba, María Itria; Andrade, Francisco; Maccaferri, Marco; Sanguineti, Maria Corinna; Tuberosa, Roberto; Guzmán, Carlos (Wiley, 2024)
In the context of climate change, high temperature is one of the main abiotic stresses hampering durum wheat production. Through the characterization of an international panel of 271 genotypes, this study investigates the effects of heat stress on quality traits and identifies which glutenins (Glu-1, Glu-2 and Glu-3 loci) alleles are the most important to obtain high gluten strength under optimal and high temperature conditions. In parallel with the wide variability observed in the panel, the genotype and environmental effects, including their interaction, showed highly significant effect on test weight, thousand kernel weight, grain protein content (GPC), sodium dodecyl sulphate sedimentation volume (SDSS) and SDSS index. Only one genotype maintained test weight and thousand kernel weight under heat-stress conditions whereas for GPC, SDSS and SDSS index, most genotypes increased values. All Glu loci had significant effects on grain protein content (with the exception of Glu-B2), SDSS and SDSS Index. None of the Glu loci interacted with the environment or years under study. Among the identified alleles, Glu-A1b, Glu-B1an, Glu-B1a, Glu-B2a, Glu-A3a.x, Glu-A3d, Glu-B3a and Glu-B3ax (including the LMW-2 pattern) were associated with high values for SDSS and SDSS Index. Genotypes identified in this study, with good performances under optimal and high temperature growing conditions, could be useful for breeding programs. The non-interaction of the Glu loci with the environment facilitates the introgression of desired alleles regardless of high growing temperatures.